2024
DOI: 10.1097/spc.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivor late-effects, chronic health problems after cancer treatment: what’s the evidence from population and registry data and where are the gaps?

Sara Faithfull,
Diana Greenfield

Abstract: Purpose of review Improvements in cancer treatment have led to more people living with and beyond a cancer diagnosis but survivors may have increased health problems as they age. The purpose of this review is to critically evaluate population data exploring incidence of late effects for cancer survivors. Recent findings 18 studies were identified between 2013 and 2023 that explored the impact on survivors’ physical and emotional health. Patients who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Of course, primary chemotherapy is not free from disadvantages. In fact, it does not attack retroperitoneal teratomas, and thus, it exposes patients to chemoresistance and relapses; in addition, these patients may suffer from cardiovascular disease and secondary malignant neoplasms [47], although relapses are uncommon with primary chemotherapy. The three chemotherapeutic agents used for this kind of neoplasm are Bleomycin, Etoposide, and Cisplatin (BEP) [48][49][50][51][52][53].…”
Section: Sexual Dysfunction After Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, primary chemotherapy is not free from disadvantages. In fact, it does not attack retroperitoneal teratomas, and thus, it exposes patients to chemoresistance and relapses; in addition, these patients may suffer from cardiovascular disease and secondary malignant neoplasms [47], although relapses are uncommon with primary chemotherapy. The three chemotherapeutic agents used for this kind of neoplasm are Bleomycin, Etoposide, and Cisplatin (BEP) [48][49][50][51][52][53].…”
Section: Sexual Dysfunction After Chemotherapymentioning
confidence: 99%
“…Sexual desire and male disappointment have been importantly considered as side effects of this kind of treatment option [36,67,68]. Orgasmic dysfunction may depend on several factors such as radiotherapy or chemotherapy; in fact, they provoke neuropathy, lower levels of testosterone related to psychological issues, and the possible use of selective serotonin inhibitors [47]. These treatments do not harm patients in every case; in fact, in the previously cited study, Bandak et al demonstrated that patients treated with BEP for testicular germ cell tumors have a preserved orgasmic phase [68].…”
Section: Sexual Dysfunction After Chemotherapymentioning
confidence: 99%
“…Specific survivorship burdens assessed were broadly categorized into five domains for organizational purposes based on common reported survivorship issues. 33 , 34 , 35 , 36 , 37 , 38 , 39 These included Neurocognition, Psychiatry, General wellness, Chronic conditions, and Treatment specific toxicities. Neurocognitive outcomes are reflected in several different categories including executive function, complex attention, language, learning, memory, and motor function.…”
Section: Definitionsmentioning
confidence: 99%
“…These drugs can have significant effects on the heart (cardiotoxicities) including prolongation of the QT interval in the cardiac cycle which increases the risk of arrhythmia, effects on LVEF, myocardial ischaemia and hypertension [5,6]. Apart from cardiac toxicities during their therapy, as more patients survive their cancer, there is increased risk of cardiovascular problems developing as a consequence of their cancer treatment [7,8]. As with heart failure in general, the underlying mechanisms for each of these toxicities varies, and the field can benefit from stratification of these different effects.…”
Section: Introduction: Cancer Vs Heart Failure In Societymentioning
confidence: 99%